Three-dimensional sensor network connectivity considering border effects and channel randomness with application to underwater networks - Mridula, K.M; Ameer, P.M (IET communications, 2018)
Connectivity is an important measure that determines the quality of service of a network. The sensor networks that find applications in underwater, terrain and space communication requires the nodes to be three-dimensional (3D), and hence, 3D connectivity is a challenging issue to be addressed. Also, the networks are prone to fading and shadowing effects due to the barriers in the communication path. Hence, the analysis of deterministic connectivity is not valid as the range of connectivity is a randomly varying parameter in the presence of fading and shadowing. In this study, the authors provide an analysis of 3D connectivity under channel randomness considering the border effects, with application to the underwater networks, where the existence of network border is significant due to the presence of natural boundaries at bottom and surface of the ocean. The connectivity analysis in the presence of log-normal shadowing is performed, and closed-form expressions are derived. Also, the 3D connectivity under the combined effects of Rayleigh fading and log-normal shadowing is analysed, which can be approximated to the well-known K-distribution used to characterise underwater sensor networks. The analysis of the proposed work matches almost exactly with the simulation, and thus, the results are validated.